High-hardness corrosion-resistant zirconium-titanium alloy and preparation method thereof
Through multiple smelting, hot forging and high-pressure solidification treatment of 47Zr-45Ti-5Al-3V alloy, a high-hardness corrosion-resistant zirconium titanium alloy was prepared, which solved the problems of insufficient impact resistance and low corrosion resistance of existing titanium alloys, and achieved It has significantly improved hardness and corrosion resistance, and is suitable for spacecraft materials.
Patent Information
- Application Number
- CN202411293934.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
AI Technical Summary
Existing titanium alloys have insufficient impact resistance and low corrosion resistance in space environments, making it difficult to meet the spacecraft's demand for high hardness and corrosion resistance.
The 47Zr-45Ti-5Al-3V alloy is prepared by a self-consumable arc furnace, and undergoes multiple smelting, hot forging and high-pressure solidification treatments to form a high-hardness corrosion-resistant zirconium titanium alloy with a hardness of more than 800HV, significantly improving corrosion resistance.
The hardness and corrosion resistance of zirconium titanium alloy have been significantly improved, and the hardness has been increased to 859HV, which has significantly enhanced corrosion resistance and is suitable for aerospace and other fields.
Smart Images

Figure CN119144857A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy materials, and in particular to a high-hardness, corrosion-resistant zirconium-titanium alloy and a preparation method thereof. Background Art
[0002] The threat of space debris to spacecraft has attracted widespread attention from the international aerospace and scientific communities. In the coming decades, taking necessary protective measures in the design of spacecraft structures will be the only effective means to deal with tiny space debris. At present, the protection of space debris mainly includes two methods: active and passive. For debris larger than 10000, radar and optical monitoring systems can be used for tracking and early warning, and spacecraft can take active evasive measures to avoid collision with them. For example, NASA made an evasive action in 2007. Compared with large debris, the number of small debris is huge, and it is difficult to effectively track and classify them with current observation methods. Only necessary protective technology can be adopted to protect spacecraft. Since a simple structural protective screen was applied in the 1980s, protective technology has developed rapidly. People have developed a variety of improved protective structures based on the structure, such as filled protective structures, multi-layer protective structures and mixed multi-layer protective structures. Filling materials are also diverse, such as fiber, fiber and foam. Hundreds of protective screens are used on the International Space Station to protect key components, including living ships and external equipment. Nevertheless, some moving parts and structural components cannot be protected due to the special structure and function and can only be exposed to the space environment. Therefore, the research and development of high-performance materials that can effectively resist the space environment is an inevitable trend in the development of spacecraft.
[0003] The materials for key moving parts and components in space are mainly made of high-strength steel, but the density of steel is relatively high, which greatly limits its usage. Titanium alloy, as a lightweight alloy, has the advantages of low density, high specific strength, good corrosion resistance, and good low-temperature performance. After more than 60 years of development, it has developed into hundreds of varieties, among which Ti-6Al-4V (TC4) is the most widely used in titanium alloys due to its excellent physical and mechanical properties, but Ti-6Al-4V has low strength and poor impact resistance. As we all know, the performance of alloys is controlled by the type and content of alloying elements. The performance of alloys can be changed by adjusting the ratio of alloy matrix elements. Therefore, it is crucial to select an alloying element that can enhance the space applicability of the alloy.
[0004] Zirconium metal belongs to Group IV in the periodic table, has the same structure as titanium, and can be infinitely dissolved. Zirconium alloy has a high melting point, a small thermal expansion coefficient, a high thermal conductivity, and moderate mechanical properties. Early studies have shown that binary alloys exhibit a strong solid solution strengthening effect, and the β phase transition temperature can be controlled by adjusting the element composition. Currently, zirconium metal is widely used in the nuclear industry and is known as the "first metal of the atomic age." Zirconium has a small thermal neutron absorption cross section and excellent resistance to neutron irradiation. In addition, zirconium also has excellent antioxidant properties. Therefore, the application prospects of zirconium and its alloys in space high-energy particle irradiation and atomic oxygen erosion environments are worth looking forward to.
[0005] The alloy overcomes the shortcomings of low hardness and low strength. Compared with traditional steel materials, the alloy not only has high hardness, but also has a density of only 2 / 3 of that of steel, and has stronger corrosion resistance, and can be used in aerospace and other fields. However, the performance of the alloy still needs to be improved, so it is urgent to study a new preparation method to maximize the hardness and corrosion resistance of titanium alloys. Summary of the invention
[0006] In order to solve the deficiencies of the above-mentioned prior art, the object of the present invention is to provide a high-hardness, corrosion-resistant zirconium-titanium alloy and a preparation method thereof. The high-hardness, corrosion-resistant zirconium-titanium alloy provided by the present invention has the advantages of high hardness and corrosion resistance. The hardness can reach above 800HV, which is a significant improvement compared to the traditional 300HV or more, and the corrosion resistance is greatly improved, and it can be applied to multiple fields such as aerospace.
[0007] Specifically, on the one hand, the present invention provides a method for preparing a high-hardness corrosion-resistant zirconium-titanium alloy, which comprises the following steps:
[0008] S1. Preparation of raw material electrodes: Select Zr, Ti, Al and V alloys and weld them into electrodes for consumable arc furnaces as raw material electrodes and reduce the vacuum degree of the consumable arc furnace to 10 -2 Below Pa;
[0009] S2, melting the raw material electrode: using a consumable arc furnace and a copper crucible to melt the raw material electrode obtained in step S1, after the raw material electrode is melted, the molten alloy is continuously dripped into the copper crucible, and an ingot is formed under the action of cooling water; then the formed ingot is welded again into an electrode of the consumable arc furnace and melted again as the raw material electrode, and the melting operation is repeated three times in total to obtain a 47Zr-45Ti-5Al-3V alloy ingot after melting;
[0010] S3, hot forging: put the 47Zr-45Ti-5Al-3V alloy ingot into the furnace and heat it to 1000-1050°C, keep it warm for 4.5-5.5 hours, and use a hydraulic press to perform three-prong and three-draw open forging treatment to form the required forged rod-shaped alloy;
[0011] S4, high pressure solidification: the forged rod-shaped alloy obtained in step S3 is subjected to high pressure solidification in a six-sided top press, the pressure of the high pressure solidification is 3-6 GPa, and then the temperature is increased and the insulation temperature is 1500-1600°C.
[0012] Preferably, the pressure of high pressure solidification in step S4 is 3 GPa, and the insulation temperature is 1600°C.
[0013] Preferably, the high pressure solidification temperature and pressure in step S4 are obtained through experiments.
[0014] Preferably, the holding time in step S4 is 15 minutes.
[0015] Preferably, in step S1 , the purity of the Zr, Ti, Al and V alloy is above 99%, and the mass ratio of the Zr, Ti, Al and V elements is 47:45:5:3.
[0016] Preferably, in step S3, the specific process of the three-drilling and three-drawing forging treatment is: roughening by 30% and then drawing by 30%, and repeating the above process three times.
[0017] Preferably, in step S3, the oxide layer formed on the surface of the alloy ingot needs to be removed after each operation is completed.
[0018] Preferably, each forging in step S3 requires that the ingot be deformed by more than 60%, and then cooled to room temperature at room temperature.
[0019] Preferably, in step S3, the 47Zr-45Ti-5Al-3V alloy ingot is placed in a furnace and heated to 1050° C., and kept warm for 5 hours.
[0020] On the other hand, the present invention provides a high hardness and corrosion-resistant zirconium-titanium alloy, which includes Zr element, Ti element, Al element and V element, and the mass ratio of the Zr element, Ti element, Al element and V element is 47:45:5:3. The high hardness and corrosion-resistant zirconium-titanium alloy is prepared by the above-mentioned preparation method.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The hardness of the high-hardness zirconium-titanium alloy prepared by the present invention is 462.4-859.08HV, which is much higher than that of ordinary alloys. The hardness of the zirconium-titanium alloy can reach above 800HV through the optimal high-pressure solidification temperature and pressure, and the corrosion resistance is greatly improved. It can be seen from the embodiments of the present invention that the hardness of the high-hardness and corrosion-resistant zirconium-titanium alloy provided by the present invention can reach up to 859HV, which is 2.26 times that of the initial alloy. The corrosion resistance is also significantly improved compared with the untreated alloy. It has excellent properties of high hardness and high corrosion resistance and can be used in multiple fields such as aviation.
[0023] (2) The method of the present invention uses 47Zr-45Ti-5Al-3V alloy as a material and processes it by a high-pressure solidification method. High-pressure solidification makes the grains of the alloy smaller and may obtain nano-scale twins. At the same time, high-pressure solidification technology can effectively shorten the atomic distance, resulting in the deformation of the electron orbit, thereby changing the electronic structure and the relationship between atoms or molecules on a microscopic scale. In addition, high-pressure technology can also increase the diffusion activation energy of atoms, reduce the diffusion rate, promote nucleation, reduce the atomic diffusion coefficient and inhibit grain growth. Compared with the traditional casting method, the sample obtained by high-pressure solidification eliminates the need for rolling or forging after casting to eliminate defects such as cast loose shrinkage cavities generated during the alloy production process. The zirconium-titanium alloy prepared by the preparation method of the present invention has excellent properties of high hardness and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The figure is a schematic diagram of the preparation method of the high-hardness and corrosion-resistant zirconium-titanium alloy of the present invention;
[0025] Figure 2 This is a SEM image of the high-strength, corrosion-resistant zirconium-titanium alloy prepared in Example 1 of the present invention;
[0026] Figure 3 This is a SEM image of the high-strength, corrosion-resistant zirconium-titanium alloy prepared in Example 2 of the present invention;
[0027] Figure 4 This is a SEM image of the high-strength, corrosion-resistant zirconium-titanium alloy prepared in Example 3 of the present invention;
[0028] Figure 5 This is a SEM image of the high-strength, corrosion-resistant zirconium-titanium alloy prepared in Example 4 of the present invention;
[0029] Figure 6 This is a SEM image of the high-strength, corrosion-resistant zirconium-titanium alloy prepared in Example 5 of the present invention;
[0030] Figure 7 This is a SEM image of the high-strength, corrosion-resistant zirconium-titanium alloy prepared in Example 6 of the present invention;
[0031] Figure 8 This is a SEM image of the high-strength, corrosion-resistant zirconium-titanium alloy prepared in Example 7 of the present invention;
[0032] Fig. 9 This is a SEM image of the high-strength and corrosion-resistant zirconium-titanium alloy prepared in Example 8 of the present invention. DETAILED DESCRIPTION
[0033] Hereinafter, embodiments of the present invention will be described with reference to the drawings.
[0034] On the one hand, the present invention provides a method for preparing a high-hardness corrosion-resistant zirconium-titanium alloy, such as Figure 1 As shown, it includes the following steps:
[0035] S1. Preparation of raw material electrodes: Select Zr, Ti, Al and V alloys and weld them into electrodes for consumable arc furnaces as raw material electrodes and reduce the vacuum degree of the consumable arc furnace to 10 -2 Below Pa.
[0036] In terms of the selection of smelting raw materials, high-purity Zr, Ti, Al and V alloys are selected and welded into electrodes for consumable arc furnaces. Secondly, a vacuum consumable arc furnace model ZHT-001 is used, and its vacuum degree is reduced to 10 -2 Pa.
[0037] S2. Melting the raw material electrode: melt the raw material electrode obtained in step S1 using a consumable arc furnace and a copper crucible. After the raw material electrode is melted, the molten alloy continuously drips into the copper crucible to form an ingot under the action of cooling water. Then, the formed ingot is welded again into an electrode of the consumable arc furnace and melted again as the raw material electrode. The raw material electrode melting operation is repeated a total of three times to make it uniform, thereby obtaining a 47Zr-45Ti-5Al-3V alloy ingot after melting.
[0038] S3. Hot forging: Place the 47Zr-45Ti-5Al-3V alloy ingot into the furnace and heat it to 1050°C. Keep it warm for 5 hours. Use a hydraulic press to perform three-stage three-draw forging. After repeated operations, the desired forged rod-shaped alloy is formed.
[0039] A 1350-ton hydraulic press was selected to perform hot forging on the smelted 47Zr-45Ti-5Al-3V alloy ingot. First, the 47Zr-45Ti-5Al-3V alloy ingot was placed in the furnace and heated to 1050°C, and kept warm for 5 hours. The hydraulic press was then used to perform three-pier and three-draw open forging. After each operation, the oxide layer formed on the surface of the alloy ingot was removed to ensure the accuracy of the next operation. In this process, each open forging must have a deformation of more than 60%, and then it is cooled to room temperature under normal temperature. Subsequently, a sample of appropriate size is selected during a forging process according to the actual operation, and the required forged rod alloy is formed after repeated operations.
[0040] In practical applications, the specific process of the three-drilling and three-drawing forging process is: roughening by 30% and then drawing by 30%, and repeating the above process three times.
[0041] S4, high pressure solidification: the forged rod-shaped alloy obtained in step S3 is subjected to high pressure solidification in a six-sided top press, the temperature of the high pressure solidification is 1500-1600° C., preferably 1600° C. The pressure of the high pressure solidification is 3-6 GPa, preferably 3 GPa.
[0042] The equipment used in this embodiment is a ZHT-001 vacuum consumable arc furnace. The raw materials are selected from Zr, Ti, Al and V raw materials with a purity of 99.9%. The raw materials are cleaned and pressed into short rod-shaped raw material blocks according to the composition ratio in Table 1. These rod-shaped raw material blocks are then welded into electrodes for the consumable arc furnace. The vacuum is evacuated to 10 -2 Pa or less, and then the ingot is melted and welded again to form an electrode for a consumable arc furnace, and melted again as a raw material electrode. The electrode melting operation is repeated three times to make it uniform.
[0043] Table 147 Composition of Zr-45Ti-5Al-3V alloy (wt%)
[0044] element Zr Ti Al V Nominal composition 47 45 5 3
[0045] In order to eliminate the possible casting structure defects of the alloy ingot after smelting, the surface of the smelted alloy ingot is coated with an antioxidant and left to stand in the air until the surface antioxidant solidifies, then placed in a heating furnace and heated to 1050°C, then kept warm for 300 minutes, and forged with an oil press, three piers and three draws are performed, and then the alloy is cooled to room temperature in the air to obtain the required forged bars. The forged 47Zr alloy sample was cut into small cylindrical samples of Φ3mm×4mm by wire cutting (a margin was required because wire cutting would produce an oxide layer on the sample surface, which required grinding with sandpaper). The zirconia round rod was processed on a lathe into a cylindrical crucible with a height of 15mm, an outer diameter of 14mm, and an inner diameter of 9mm; the boron nitride round rod was processed into cylindrical crucibles with a height of 15mm, an outer diameter of 9mm, an inner diameter of 7mm and a height of 4mm, an outer diameter of 7mm, and an inner diameter of 3mm; the graphite rods were processed into graphite sheets of Φ14mm×2.5mm and Φ7mm×5.5mm, respectively, and finally they were assembled in a pyrophyllite block with a pore size of 14mm and placed in a six-sided top press for high-pressure solidification experiments.
[0046] The forged rod alloy is cut into Φ3mm×4mm alloy cylinders by electric spark wire cutting. Because the outer oxide scale needs to be polished off after cutting, pay attention to leaving some margin when cutting. At the same time, the zirconia rod, boron nitride rod and carbon rod are turned into the sizes in Table 2. After assembly, the sample, together with the crucible and the conductive steel cap, are placed in a 14mm pyrophyllite block. The conductive steel cap needs to be polished with sandpaper before use to remove the oxide layer and enhance conductivity. The materials needed are placed in an electric heating blower and dried overnight the day before high-pressure solidification to prevent the materials from getting wet. Then the pyrophyllite block is placed in a six-sided top press for high-pressure solidification experiments.
[0047] Table 2 Dimensions of various parts of the crucible
[0048] name Outer diameter / mm Inner diameter / mm Height / mm Zirconia Crucible 14 9 15 Boron nitride crucible 1 9 7 15 Boron nitride crucible 2 7 3 4 Graphite sheet 1 14 - 2.5 Graphite sheet 2 7 - 5.5
[0049] By changing the high pressure solidification treatment conditions, 47Zr-45Ti-5Al-3V alloys with different treatment conditions were obtained, and the optimal pressure and temperature were selected. Pressure is an important thermodynamic parameter affecting the alloy solidification process, and high pressure solidification can change the phase diffusion coefficient and obtain non-equilibrium structure.
[0050] 47Zr-45Ti-5Al-3V alloy is used as the material and is processed by the method of high pressure solidification (HPS). High pressure solidification makes the grains of the alloy smaller and may obtain nano-scale twins. At the same time, high pressure solidification technology can effectively shorten the atomic distance, resulting in the deformation of the electron orbit, thereby changing the electronic structure and the relationship between atoms or molecules on a microscopic scale. In addition, high pressure technology can also increase the diffusion activation energy of atoms, reduce the diffusion rate, promote nucleation, reduce the atomic diffusion coefficient and inhibit grain growth. Compared with traditional casting methods, the samples obtained by high pressure solidification eliminate the need for rolling or forging after casting to eliminate defects such as cast loose shrinkage cavities generated during the alloy production process. The zirconium-titanium alloy provided by the present invention has excellent properties of high hardness and corrosion resistance. The results of the embodiments show that the high hardness of the high-hardness and corrosion-resistant zirconium-titanium alloy provided by the present invention refers to a maximum hardness of 859HV. The hardness of the high-hardness and corrosion-resistant zirconium-titanium alloy is 2.26 times that of the initial alloy, and the corrosion resistance is significantly improved compared to the untreated 47Zr-45Ti-5Al-3V.
[0051] In a specific embodiment of the present invention, the high pressure solidification treatment is preferably carried out in a CS-1B type synthetic diamond six-sided top press. The present invention can make the composition of the alloy ingot more uniform and have fewer defects after hot forging treatment.
[0052] After the sample is dried and assembled, it is placed in a six-sided artificial diamond press to pressurize the sample, and the pressure is preferably 3GPa, and then the power is manually increased and the temperature is increased. The optimal temperature for insulation is 1600°C, and the insulation time is 15 minutes. In a specific embodiment of the present invention, the power is manually increased by 100W each time, and 50W each time after 1500W.
[0053] On the other hand, the present invention provides a high-hardness and corrosion-resistant zirconium-titanium alloy, which comprises Zr, Ti, Al and V, wherein the mass ratio of Zr, Ti, Al and V is 47:45:5:3. The zirconium-titanium alloy obtained by the preparation method of the present invention has excellent properties of high hardness and corrosion resistance.
[0054] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] Example 1
[0056] Select high-purity Zr, Ti, Al and V alloys and weld them into electrodes for consumable arc furnaces. Use a vacuum consumable arc furnace model ZHT-001 and reduce its vacuum degree to 10 -2 Pa. Then, a water-cooled copper crucible and the electrode of the consumable arc furnace prepared above are used to melt the raw material electrode. Subsequently, the raw material electrode begins to melt, and the molten alloy drips into the copper crucible continuously, forming an ingot under the action of cooling water. Finally, the formed ingot is welded again into the electrode of the consumable arc furnace, and it is melted again as the raw material electrode, and the above operation is repeated three times to make it uniform.
[0057] A 1350-ton hydraulic press was selected to perform hot forging on the smelted 47Zr-45Ti-5Al-3V alloy ingot. First, the 47Zr-45Ti-5Al-3V alloy ingot was placed in the furnace and heated to 1050°C, and kept warm for 5 hours. The hydraulic press was then used to perform three-pier and three-draw open forging. After each operation, the oxide layer formed on the surface of the alloy ingot was removed to ensure the accuracy of the next operation. In this process, each open forging must have a deformation of more than 60%, and then it is cooled to room temperature under normal temperature. Subsequently, a sample of appropriate size is selected during a forging process according to the actual operation, and the required forged rod alloy is formed after repeated operations.
[0058] The forged alloy ingot was cut into alloy cylinders with a diameter of 3 mm and a height of 4 mm by wire cutting with electric sparks, and the zirconium oxide rod, boron nitride rod and carbon rod were turned into appropriate sizes. After being assembled with the alloy cylinder, the sample, crucible and conductive steel cap were placed in a pyrophyllite block with a hole diameter of 14 mm.
[0059] After the sample is dried and assembled, it is placed in a six-sided artificial diamond press to pressurize the sample to a processing pressure of 3 GPa, and then the power is manually increased to increase the temperature, and the insulation temperature is 1500°C for 15 minutes. After the insulation is completed, the emergency stop button is pressed, and after the hammer head of the press is cooled, the sample is taken out to obtain the high-hardness and corrosion-resistant alloy of the present invention.
[0060] Figure 2 This is a SEM image of the high-hardness, strong and corrosion-resistant zirconium-titanium alloy prepared in Example 1 of the present invention, wherein the black matrix is the β phase, the white dendrites are the α phase, and the fine needle-like structure is the α″ phase. The fine white particles on the matrix are the ω phase. The black strip-like structure is the primary α phase. The ω phase is a close-packed hexagonal structure with high hardness, which can ensure that the alloy has the characteristics of high hardness.
[0061] Example 2
[0062] Select high-purity Zr, Ti, Al and V alloys and weld them into electrodes for consumable arc furnaces. Use a vacuum consumable arc furnace model ZHT-001 and reduce its vacuum degree to 10 -2 Pa. Again, the raw material electrode is melted using a water-cooled copper crucible and the electrode of the consumable arc furnace made in the first step. Subsequently, the raw material electrode begins to melt, and the molten alloy drips into the copper crucible continuously, forming an ingot under the action of cooling water. Finally, the formed ingot is welded again into the electrode of the consumable arc furnace, and it is melted again as the raw material electrode. The operation is repeated three times to make it uniform.
[0063] A 1350-ton hydraulic press was selected to perform hot forging on the smelted 47Zr-45Ti-5Al-3V alloy ingot. First, the 47Zr-45Ti-5Al-3V alloy ingot was placed in the furnace and heated to 1050°C, and kept warm for 5 hours. The hydraulic press was then used to perform three-pier and three-draw open forging. After each operation, the oxide layer formed on the surface of the alloy ingot was removed to ensure the accuracy of the next operation. In this process, each open forging must have a deformation of more than 60%, and then it is cooled to room temperature under normal temperature. Subsequently, a sample of appropriate size is selected during a forging process according to the actual operation, and the required forged rod alloy is formed after repeated operations.
[0064] The forged alloy ingot was cut into alloy cylinders with a diameter of 3 mm and a height of 4 mm by wire cutting with electric sparks, and the zirconium oxide rod, boron nitride rod and carbon rod were turned into appropriate sizes. After assembly, the sample, together with the crucible and the conductive steel cap, was placed in a pyrophyllite block with a hole diameter of 14 mm.
[0065] After the sample is dried and assembled, it is placed in a six-sided artificial diamond press to pressurize the sample to a processing pressure of 3 GPa, and then the power is manually increased to heat up, and the insulation temperature is 1600°C for 15 minutes. After the insulation is completed, the emergency stop button is pressed, and after the hammer head of the press is cooled, the sample is taken out to obtain the high-hardness and corrosion-resistant alloy of the present invention.
[0066] Figure 3 This is a SEM image of the high-hardness, strong and corrosion-resistant zirconium-titanium alloy prepared in Example 2 of the present invention, wherein the black matrix is the β phase, the white dendrites are the α phase, and the fine needle-like structure is the α″ phase. The fine white particles on the matrix are the ω phase. The black strip-like structure is the primary α phase. The ω phase is a close-packed hexagonal structure with high hardness, which can ensure that the alloy has the characteristics of high hardness.
[0067] Example 3
[0068] Select high-purity Zr, Ti, Al and V alloys and weld them into electrodes for consumable arc furnaces. Use a vacuum consumable arc furnace model ZHT-001 and reduce its vacuum degree to 10 -2 Pa. Again, the raw material electrode is melted using a water-cooled copper crucible and the electrode of the consumable arc furnace made in the first step. Subsequently, the raw material electrode begins to melt, and the molten alloy drips into the copper crucible continuously, forming an ingot under the action of cooling water. Finally, the formed ingot is welded again into the electrode of the consumable arc furnace, and it is melted again as the raw material electrode. The operation is repeated three times to make it uniform.
[0069] A 1350-ton hydraulic press was selected to perform hot forging on the smelted 47Zr-45Ti-5Al-3V alloy ingot. First, the 47Zr-45Ti-5Al-3V alloy ingot was placed in the furnace and heated to 1050°C, and kept warm for 5 hours. The hydraulic press was then used to perform three-pier and three-draw open forging. After each operation, the oxide layer formed on the surface of the alloy ingot was removed to ensure the accuracy of the next operation. In this process, each open forging must have a deformation of more than 60%, and then it is cooled to room temperature under normal temperature. Subsequently, a sample of appropriate size is selected during a forging process according to the actual operation, and the required forged rod alloy is formed after repeated operations.
[0070] The forged alloy ingot was cut into alloy cylinders with a diameter of 3 mm and a height of 4 mm by wire cutting with electric sparks, and the zirconium oxide rod, boron nitride rod and carbon rod were turned into appropriate sizes. After assembly, the sample, together with the crucible and the conductive steel cap, was placed in a pyrophyllite block with a hole diameter of 14 mm.
[0071] After the sample is dried and assembled, it is placed in a six-sided artificial diamond press to pressurize the sample to a processing pressure of 4 GPa, and then the power is manually increased to increase the temperature, and the insulation temperature is 1500°C for 15 minutes. After the insulation is completed, the emergency stop button is pressed, and after the hammer head of the press is cooled, the sample is taken out to obtain the high-hardness and corrosion-resistant alloy of the present invention.
[0072] Figure 4 This is a SEM image of the high-hardness, strong and corrosion-resistant zirconium-titanium alloy prepared in Example 3 of the present invention, wherein the black matrix is the β phase, the white dendrites are the α phase, and the fine needle-like structure is the α″ phase. The fine white particles on the matrix are the ω phase. The black strip-like structure is the primary α phase. The ω phase is a close-packed hexagonal structure with high hardness, which can ensure that the alloy has the characteristics of high hardness.
[0073] Example 4
[0074] Select high-purity Zr, Ti, Al and V alloys and weld them into electrodes for consumable arc furnaces. Use a vacuum consumable arc furnace model ZHT-001 and reduce its vacuum degree to 10 -2 Pa. Again, the raw material electrode is melted using a water-cooled copper crucible and the electrode of the consumable arc furnace made in the first step. Subsequently, the raw material electrode begins to melt, and the molten alloy drips into the copper crucible continuously, forming an ingot under the action of cooling water. Finally, the formed ingot is welded again into the electrode of the consumable arc furnace, and it is melted again as the raw material electrode. The operation is repeated three times to make it uniform.
[0075] A 1350-ton hydraulic press was selected to perform hot forging on the smelted 47Zr-45Ti-5Al-3V alloy ingot. First, the 47Zr-45Ti-5Al-3V alloy ingot was placed in the furnace and heated to 1050°C, and kept warm for 5 hours. The hydraulic press was then used to perform three-pier and three-draw open forging. After each operation, the oxide layer formed on the surface of the alloy ingot was removed to ensure the accuracy of the next operation. In this process, each open forging must have a deformation of more than 60%, and then it is cooled to room temperature under normal temperature. Subsequently, a sample of appropriate size is selected during a forging process according to the actual operation, and the required forged rod alloy is formed after repeated operations.
[0076] The forged alloy ingot was cut into alloy cylinders with a diameter of 3 mm and a height of 4 mm by wire cutting with electric sparks, and the zirconium oxide rod, boron nitride rod and carbon rod were turned into appropriate sizes. After assembly, the sample, together with the crucible and the conductive steel cap, was placed in a pyrophyllite block with a hole diameter of 14 mm.
[0077] After the sample is dried and assembled, it is placed in a six-sided artificial diamond press to pressurize the sample to a processing pressure of 4 GPa, and then the power is manually increased to increase the temperature, and the insulation temperature is 1600°C for 15 minutes. After the insulation is completed, the emergency stop button is pressed, and after the hammer head of the press is cooled, the sample is taken out to obtain the high-hardness and corrosion-resistant alloy of the present invention.
[0078] Figure 5 This is a SEM image of the high-hardness, strong and corrosion-resistant zirconium-titanium alloy prepared in Example 4 of the present invention, wherein the black matrix is the β phase, the white dendrites are the α phase, and the fine needle-like structure is the α″ phase. The fine white particles on the matrix are the ω phase. The black strip-like structure is the primary α phase. The ω phase is a close-packed hexagonal structure with high hardness, which can ensure that the alloy has the characteristics of high hardness.
[0079] Example 5
[0080] Select high-purity Zr, Ti, Al and V alloys and weld them into electrodes for consumable arc furnaces. Use a vacuum consumable arc furnace model ZHT-001 and reduce its vacuum degree to 10 -2 Pa. Again, the raw material electrode is melted using a water-cooled copper crucible and the electrode of the consumable arc furnace made in the first step. Subsequently, the raw material electrode begins to melt, and the molten alloy drips into the copper crucible continuously, forming an ingot under the action of cooling water. Finally, the formed ingot is welded again into the electrode of the consumable arc furnace, and it is melted again as the raw material electrode. The operation is repeated three times to make it uniform.
[0081] A 1350-ton hydraulic press was selected to perform hot forging on the smelted 47Zr-45Ti-5Al-3V alloy ingot. First, the 47Zr-45Ti-5Al-3V alloy ingot was placed in the furnace and heated to 1050°C, and kept warm for 5 hours. The hydraulic press was then used to perform three-pier and three-draw open forging. After each operation, the oxide layer formed on the surface of the alloy ingot was removed to ensure the accuracy of the next operation. In this process, each open forging must have a deformation of more than 60%, and then it is cooled to room temperature under normal temperature. Subsequently, a sample of appropriate size is selected during a forging process according to the actual operation, and the required forged rod alloy is formed after repeated operations.
[0082] The forged alloy ingot was cut into alloy cylinders with a diameter of 3 mm and a height of 4 mm by wire cutting with electric sparks, and the zirconium oxide rod, boron nitride rod and carbon rod were turned into appropriate sizes. After assembly, the sample, together with the crucible and the conductive steel cap, was placed in a pyrophyllite block with a hole diameter of 14 mm.
[0083] After the sample is dried and assembled, it is placed in a six-sided artificial diamond press to pressurize the sample to a processing pressure of 5 GPa, and then the power is manually increased to increase the temperature, and the insulation temperature is 1500°C for 15 minutes. After the insulation is completed, the emergency stop button is pressed, and after the hammer head of the press is cooled, the sample is taken out to obtain the high-hardness and corrosion-resistant alloy of the present invention.
[0084] Figure 6 This is a SEM image of the high-hardness, strong and corrosion-resistant zirconium-titanium alloy prepared in Example 5 of the present invention, wherein the black matrix is the β phase, the white dendrites are the α phase, and the fine needle-like structure is the α″ phase. The fine white particles on the matrix are the ω phase. The black strip-like structure is the primary α phase. The ω phase is a close-packed hexagonal structure with high hardness, which can ensure that the alloy has the characteristics of high hardness.
[0085] Example 6
[0086] Select high-purity Zr, Ti, Al and V alloys and weld them into electrodes for consumable arc furnaces. Use a vacuum consumable arc furnace model ZHT-001 and reduce its vacuum degree to 10 -2 Pa. Again, the raw material electrode is melted using a water-cooled copper crucible and the electrode of the consumable arc furnace made in the first step. Subsequently, the raw material electrode begins to melt, and the molten alloy drips into the copper crucible continuously, forming an ingot under the action of cooling water. Finally, the formed ingot is welded again into the electrode of the consumable arc furnace, and it is melted again as the raw material electrode. The operation is repeated three times to make it uniform.
[0087] A 1350-ton hydraulic press was selected to perform hot forging on the smelted 47Zr-45Ti-5Al-3V alloy ingot. First, the 47Zr-45Ti-5Al-3V alloy ingot was placed in the furnace and heated to 1050°C, and kept warm for 5 hours. The hydraulic press was then used to perform three-pier and three-draw open forging. After each operation, the oxide layer formed on the surface of the alloy ingot was removed to ensure the accuracy of the next operation. In this process, each open forging must have a deformation of more than 60%, and then it is cooled to room temperature under normal temperature. Subsequently, a sample of appropriate size is selected during a forging process according to the actual operation, and the required forged rod alloy is formed after repeated operations.
[0088] The forged alloy ingot was cut into alloy cylinders with a diameter of 3 mm and a height of 4 mm by wire cutting with electric sparks, and the zirconium oxide rod, boron nitride rod and carbon rod were turned into appropriate sizes. After assembly, the sample, together with the crucible and the conductive steel cap, was placed in a pyrophyllite block with a hole diameter of 14 mm.
[0089] After the sample is dried and assembled, it is placed in a six-sided artificial diamond press to pressurize the sample to a processing pressure of 5 GPa, and then the power is manually increased to increase the temperature, and the insulation temperature is 1600°C for 15 minutes. After the insulation is completed, the emergency stop button is pressed, and after the hammer head of the press is cooled, the sample is taken out to obtain the high-hardness and corrosion-resistant alloy of the present invention.
[0090] Figure 7 This is a SEM image of the high-hardness, strong and corrosion-resistant zirconium-titanium alloy prepared in Example 6 of the present invention, wherein the black matrix is the β phase, the white dendrites are the α phase, and the fine needle-like structure is the α″ phase. The fine white particles on the matrix are the ω phase. The black strip-like structure is the primary α phase. The ω phase is a close-packed hexagonal structure with high hardness, which can ensure that the alloy has the characteristics of high hardness.
[0091] Example 7
[0092] Select high-purity Zr, Ti, Al and V alloys and weld them into electrodes for consumable arc furnaces. Use a vacuum consumable arc furnace model ZHT-001 and reduce its vacuum degree to 10 -2 Pa. Again, the raw material electrode is melted using a water-cooled copper crucible and the electrode of the consumable arc furnace made in the first step. Subsequently, the raw material electrode begins to melt, and the molten alloy drips into the copper crucible continuously, forming an ingot under the action of cooling water. Finally, the formed ingot is welded again into the electrode of the consumable arc furnace, and it is melted again as the raw material electrode. The operation is repeated three times to make it uniform.
[0093] A 1350-ton hydraulic press was selected to perform hot forging on the smelted 47Zr-45Ti-5Al-3V alloy ingot. First, the 47Zr-45Ti-5Al-3V alloy ingot was placed in the furnace and heated to 1050°C, and kept warm for 5 hours. The hydraulic press was then used to perform three-pier and three-draw open forging. After each operation, the oxide layer formed on the surface of the alloy ingot was removed to ensure the accuracy of the next operation. In this process, each open forging must have a deformation of more than 60%, and then it is cooled to room temperature under normal temperature. Subsequently, a sample of appropriate size is selected during a forging process according to the actual operation, and the required forged rod alloy is formed after repeated operations.
[0094] The forged alloy ingot was cut into alloy cylinders with a diameter of 3 mm and a height of 4 mm by wire cutting with electric sparks, and the zirconium oxide rod, boron nitride rod and carbon rod were turned into appropriate sizes. After assembly, the sample, together with the crucible and the conductive steel cap, was placed in a pyrophyllite block with a hole diameter of 14 mm.
[0095] After the sample is dried and assembled, it is placed in a six-sided artificial diamond press to pressurize the sample to a processing pressure of 6 GPa, and then the power is manually increased to heat up, and the insulation temperature is 1500°C for 15 minutes. After the insulation is completed, the emergency stop button is pressed, and after the hammer head of the press is cooled, the sample is taken out to obtain the high-hardness and corrosion-resistant alloy of the present invention.
[0096] Figure 8 This is a SEM image of the high-hardness, strong and corrosion-resistant zirconium-titanium alloy prepared in Example 7 of the present invention, wherein the black matrix is the β phase, the white dendrites are the α phase, and the fine needle-like structure is the α″ phase. The fine white particles on the matrix are the ω phase. The black strip-like structure is the primary α phase. The ω phase is a close-packed hexagonal structure with high hardness, which can ensure that the alloy has the characteristics of high hardness.
[0097] Example 8
[0098] Select high-purity Zr, Ti, Al and V alloys and weld them into electrodes for consumable arc furnaces. Use a vacuum consumable arc furnace model ZHT-001 and reduce its vacuum degree to 10 -2 Pa. Again, the raw material electrode is melted using a water-cooled copper crucible and the electrode of the consumable arc furnace made in the first step. Subsequently, the raw material electrode begins to melt, and the molten alloy drips into the copper crucible continuously, forming an ingot under the action of cooling water. Finally, the formed ingot is welded again into the electrode of the consumable arc furnace, and it is melted again as the raw material electrode. The operation is repeated three times to make it uniform.
[0099] A 1350-ton hydraulic press was selected to perform hot forging on the smelted 47Zr-45Ti-5Al-3V alloy ingot. First, the 47Zr-45Ti-5Al-3V alloy ingot was placed in the furnace and heated to 1050°C, and kept warm for 5 hours. The hydraulic press was then used to perform three-pier and three-draw open forging. After each operation, the oxide layer formed on the surface of the alloy ingot was removed to ensure the accuracy of the next operation. In this process, each open forging must have a deformation of more than 60%, and then it is cooled to room temperature under normal temperature. Subsequently, a sample of appropriate size is selected during a forging process according to the actual operation, and the required forged rod alloy is formed after repeated operations.
[0100] The forged alloy ingot was cut into alloy cylinders with a diameter of 3 mm and a height of 4 mm by wire cutting with electric sparks, and the zirconium oxide rod, boron nitride rod and carbon rod were turned into appropriate sizes. After assembly, the sample, together with the crucible and the conductive steel cap, was placed in a pyrophyllite block with a hole diameter of 14 mm.
[0101] After the sample is dried and assembled, it is placed in a six-sided artificial diamond press to pressurize the sample to a processing pressure of 6 GPa, and then the power is manually increased to increase the temperature, and the insulation temperature is 1600°C for 15 minutes. After the insulation is completed, the emergency stop button is pressed, and after the hammer head of the press is cooled, the sample is taken out to obtain the high-hardness and corrosion-resistant alloy of the present invention.
[0102] Fig. 9 This is a SEM image of the high-hardness, corrosion-resistant zirconium-titanium alloy prepared in Example 8 of the present invention, wherein the black matrix is the β phase, the white dendrites are the α phase, and the fine needle-like structure is the α″ phase. The fine white particles on the matrix are the ω phase. The black strip-like structure is the primary α phase. The ω phase is a close-packed hexagonal structure with high hardness, which can ensure that the alloy has the characteristics of high hardness.
[0103] Test Example 1
[0104] The hardness performance test of the products of Examples 1-8 was carried out according to GB / T4340.4-2009 "Vickers hardness test for metallic materials". The results are listed in Table 3. From the data in Table 3, it can be concluded that the hardness of the high hardness zirconium-titanium alloy prepared in Examples 1-8 of the present invention is 462.4-859.08 HV.
[0105] Table 3 Hardness test results of the alloys prepared in Examples 1 to 8.
[0106] Example Hardness (HV) 1 579.12 2 859.08 3 529.83 4 735.89 5 500.67 6 680.98 7 462.4 8 539.02
[0107] Test Example 2
[0108] This experiment uses the CHI660E electrochemical workstation of Shanghai Chenhua Instrument Co., Ltd. to carry out corrosion tests. The electrolyte solution is a 3.5wt% sodium chloride solution with a corrosion temperature of 37°C. Before the test, the copper wire and the sample are connected together by soldering, and then the unsoldered side is used as the bottom surface for cold embedding. In order to ensure that the area of the sample exposed in the electrolyte is the same, the embedded side needs to be polished to the maximum cross-section of the cylinder to ensure that there are no scratches on the surface of the sample, and it is cleaned with acetone and deionized water. The experiment uses a three-electrode test system. The open circuit potential is also called the corrosion potential, that is, the electrode potential of the sample in the absence of an external current. In order to obtain a stable open circuit voltage, the sample needs to be placed in the electrolyte in advance so that the two can reach a stable state for the smooth progress of the experiment.
[0109] The Tafel polarization curve records the relationship between the logarithm of the current and the potential or time. The scanning range of the curve is -1V (SCE) ~ 3V (SCE), and the scanning speed is 1mV / s.
[0110] AC impedance is a very important electrochemical test method, which refers to the analysis of material surface phenomena by controlling the sine wave current to vibrate within a small amplitude and measuring the corresponding experimental parameters. The test frequency range is 0.01-105Hz, and the AC voltage amplitude is 10mV. The test results of the corrosion potential and corrosion current of the alloy in 3.5wt% sodium chloride solution are shown in Table 4.
[0111] Table 4 Test results of corrosion potential and corrosion current of alloys of Examples 1 to 8 in 3.5wt% sodium chloride solution
[0112] Example Self-corrosion potential (mV) <![CDATA[Corrosion current density (A / cm 2 )]]> 1 -350 <![CDATA[1.115×10 -5 ]]> 2 -358 <![CDATA[1.245×10 -5 ]]> 3 -359 <![CDATA[1.328×10 -5 ]]> 4 -387 <![CDATA[1.794×10 -5 ]]> 5 -382 <![CDATA[1.492×10 -5 ]]> 6 -322 <![CDATA[5.077×10 -6 ]]> 7 -352 <![CDATA[1.191×10 -5 ]]> 8 -283 <![CDATA[1.776×10 -6 ]]>
[0113] From Table 2, it can be seen that the two optimal values of the self-corrosion potential and corrosion current density of the alloy, as well as its pitting resistance, it can be found that the corrosion resistance of the 47Zr alloy after high pressure solidification at 6GPa and 1600°C is better. The parameter values of the equivalent circuit diagram of the alloys of Examples 1 to 8 are shown in Table 5.
[0114] Table 5 Parameters of equivalent circuit diagram of alloys of Examples 1 to 8
[0115]
[0116] It can be seen from the table that the value of the electrolyte resistance Rs is stable at 17Ω·cm 2 The Rct value depends on the corrosion resistance of the alloy. The larger the Rct value, the more corrosion-resistant the alloy is. The fitting results are basically consistent with the results of the potentiodynamic polarization curve.
[0117] The embodiments described above are only descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a high-hardness, corrosion-resistant zirconium-titanium alloy, characterized in that: It includes the following steps: S1. Preparation of raw material electrodes: Select Zr, Ti, Al and V alloys and weld them into electrodes for consumable arc furnaces as raw material electrodes and reduce the vacuum degree of the consumable arc furnace to 10 -2 Below Pa; S2, melting the raw material electrode: using a consumable arc furnace and a copper crucible to melt the raw material electrode obtained in step S1, after the raw material electrode is melted, the molten alloy is continuously dripped into the copper crucible, and an ingot is formed under the action of cooling water; then the formed ingot is welded again into an electrode of the consumable arc furnace and melted again as the raw material electrode, and the melting operation is repeated three times in total to obtain a smelted alloy ingot; S3, hot forging: put the alloy ingot into the furnace and heat it to 1000-1050℃, keep it warm for 4.5-5.5 hours, and use a hydraulic press to perform three-prong and three-draw forging to form the required forged rod-shaped alloy; S4, high pressure solidification: the forged rod-shaped alloy obtained in step S3 is subjected to high pressure solidification in a six-sided top press, the pressure of the high pressure solidification is 3-6 GPa, and then the temperature is increased and the insulation temperature is 1500-1600°C.
2. The method for preparing a high-hardness, corrosion-resistant zirconium-titanium alloy according to claim 1, characterized in that: The pressure of high pressure solidification in step S4 is 3 GPa, and the insulation temperature is 1600°C.
3. The method for preparing a high-hardness, corrosion-resistant zirconium-titanium alloy according to claim 1, characterized in that: The high pressure solidification temperature and pressure in step S4 are obtained through experiments.
4. The method for preparing a high-hardness, corrosion-resistant zirconium-titanium alloy according to claim 1, characterized in that: The holding time in step S4 is 15 min.
5. The method for preparing a high-hardness, corrosion-resistant zirconium-titanium alloy according to claim 1, characterized in that: In step S1, the purity of the Zr, Ti, Al and V alloy is above 99%, and the mass ratio of the Zr, Ti, Al and V elements is 47:45:5:
3.
6. The method for preparing a high-hardness, corrosion-resistant zirconium-titanium alloy according to claim 1, characterized in that: In step S3, the specific process of the three-drilling and three-drawing forging treatment is: roughening by 30% and then drawing by 30%, and repeating the above process three times.
7. The method for preparing a high-hardness, corrosion-resistant zirconium-titanium alloy according to claim 6, characterized in that: In step S3, the oxide layer formed on the surface of the alloy ingot needs to be removed after each operation is completed.
8. The method for preparing a high-hardness, corrosion-resistant zirconium-titanium alloy according to claim 7, characterized in that: In step S3, each forging operation must cause the ingot to be deformed by more than 60%, and then the ingot is cooled to room temperature under normal temperature conditions.
9. The method for preparing a high-hardness, corrosion-resistant zirconium-titanium alloy according to claim 1, characterized in that: In step S3, the 47Zr-45Ti-5Al-3V alloy ingot is placed in a furnace and heated to 1050° C., and then kept warm for 5 hours.
10. A high-hardness, corrosion-resistant zirconium-titanium alloy prepared by the method for preparing a high-hardness, corrosion-resistant zirconium-titanium alloy according to claim 1, characterized in that: It includes Zr element, Ti element, Al element and V element, and the mass ratio of Zr element, Ti element, Al element and V element is 47:45:5:
3. The high-hardness and corrosion-resistant zirconium-titanium alloy is prepared by the above preparation method.
